Vortex Dynamics From Physical to Mathematical Aspects - Bakırtaş, İlkay; Antar, Nalan (IntechOpen, 2022)
This book discusses vortex dynamics theory from physics, mathematics, and engineering perspectives. It includes nine chapters that cover a variety of research results related to vortex dynamics including nonlinear optics, fluid dynamics, and plasma physics.